Isles of the emberdark - Sanderson, Brandon (Sanderson, Brandon. Cosmere novel., 2026)
"All his life, Sixth of the Dusk has been a traditional trapper of Aviar--the supernatural birds his people bond with--on the deadly island of Patji. Then one fateful night he propels his people into arace to modernize before they can be conquered by the Ones Above, invaders from the stars who want to exploit the Aviar. But it's a race they're losing, and Dusk fears his people will lose themselves in the effort. When a chance comes to sail into the expanse of the emberdark beyond a mystical portal, Dusk sets off to find his people's salvation with only a canoe, his birds, and all the grit and canniness of a Patji trapper"--